(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
KhushwantSingh’s Train To Pakistan pictures the brutal, realistic story of politicalhatred, and of mass passions during the tragic days that preceded and followedthe partition of India. ` distorted the political judgments. Worst of all, itderanged the understanding of the morel rightness of the people.